Growth hormone/IGF‐1 axis longitudinal evaluation in clinically isolated syndrome patients on interferon β‐1b therapy: stimulation tests and correlations with clinical and radiological conversion to multiple sclerosis. (16th December 2016) - Lanzillo, R.; Di Somma, C.; Quarantelli, M.; Carotenuto, A.; Pivonello, C.; Moccia, M.; Cianflone, A.; Marsili, A.; Puorro, G.; Saccà, F.; Russo, C. V.; De Luca Picione, C.; et al.
Abstract : Background and purpose: Growth hormone (GH)/insulin‐like growth factor 1 (IGF‐1) axis abnormalities in multiple sclerosis (MS) suggest their role in its pathogenesis. Interferon β (IFN‐β) efficacy could be mediated also by an increase of IGF‐1 levels. A 2‐year longitudinal study was performed to estimate the prevalence of GH and/or IGF‐1 deficiency in clinically isolated syndrome (CIS) patients and their correlation with conversion to MS in IFN treated patients. Methods: Clinical and demographic features of CIS patients were collected before the start of IFN‐β‐1b. IGF‐1 levels and GH response after arginine and GH releasing hormone + arginine stimulation tests were assessed. Clinical and magnetic resonance imaging evaluations were performed at baseline, 1 year and 2 years. Results: Thirty CIS patients (24 female) were enrolled. At baseline, four patients (13%) showed a hypothalamic GH deficiency (GHD), whilst no one had a pituitary GHD. Baseline demographic, clinical and radiological data were not related to GHD, whilst IGF‐1 levels were inversely related to age ( P < 0.001) and GH levels ( P = 0.03). GH and IGF‐1 serum mean levels were not significantly modified after 1 and 2 years of treatment in the whole group, although 3/4 GHD patients experienced a normalization of GH levels, whilst one dropped out. After 2 years of treatment 13/28 (46%) patients converted to MS. The presence of GHD and GH and IGF‐1 levels were not predictive of relapses, new T2 lesions or conversion occurrence. Conclusions: Growth hormone/IGF‐1 axis function was found to be frequently altered in CIS patients, but this was not related to MS conversion. Patients experienced an improvement of GHD during IFN therapy. Longer follow‐up is necessary to assess its impact on disease progression.